Pengaruh Model Inkuiri Terbimbing Berbasis Kearifan Lokal Terhadap Kemampuan Berpikir Kritis Tema Pahlawanku Kelas IV Sekolah Dasar - Lenni Sofiannida; Sri Utaminingsih; Su`ad Su`ad (Universitas Muria Kudus, 2018)
The purpose of this study was to determine the effect of guided inquiry based on local wisdom on students cticical thinking skills in the theme of my hero in grade IV elementary school. The type of research used is the experiment with the Pretest Posttest Only Group Design. The sample in this study was grade IV elementary school in Undaan district, Kudus district. The instrument used are tests and observation and documentation. The results of this sudy indicate that: 1) the model of guided inquiry based on local wisdom is effective to improve critical thinking skills in the theme of my hero class IV elementary school rather than guided inquiry models. This is evidenced by the results of the mean value of guided inquiry models based on local wisdom rather than guided inquiry models (76,55 bigger than 67,94), 2) there is a significant effect of students critical thinking skills between the model of guided inquiry based on local wisdom and the guided inqiry model. This is evidenced by the results of t caount bigger than t table (2,757 bigger than 2, 002) and smaller significance value with a significance level of 5% (p = 0,010 bigger than 0,05).